ANTIPYRETIC ACTIVITY OF HYDRO-METHANOLIC EXTRACT OF TRACHYSPERMUM AMMI LINN. SEEDS IN RABBITS (Pakistan Journal of Science, 2022)
Antipyretic activity of hydro-methanol extract of Tachyspermum ammi Linn. seeds at dose 250mg/Kg and 500mg/Kg was determined in experimental animals. Yeast induced pyrexia method was used. Paracetamol (150 mg/Kg, p.o.) was used as standard drug. Rectal temperatures of rabbits were measured before the administration of extract, vehicle and paracetamol, and repeated at one-hour interval up to six hours by digital thermometer. Phytochemical analysis was carried out on extract to determine the existing groups. The extract dose 500 mg/Kg significantly reduces the elevated temperature. Phytochemical screening showed that flavonoids, alkaloids, phenols, anthraquinones, glycosides, tannins, phenols and saponins are present in the extract. The results showed hydro-methanol extract of Trachyspermum ammi L. exhibited a significant antipyretic effect and its efficacy was similar to standard antipyretic drug Paracetamol.
Keywords: Antipyretic activity; medicinal plants; hydro-methanol extract; medicinal plants and rabbits